1994
DOI: 10.3354/meps107211
|View full text |Cite
|
Sign up to set email alerts
|

The importance of predators on a sandflat: interplay between seasonal changes in prey densities and predator effects

Abstract: An experiment was designed to assess the role of 2 different predators in determining the macrobenthic community structure of an intertidal sandflat. The 2 predators were: shorebirds which feed throughout the year by removing individual prey items, and eagle rays Myliobatis tenuicaudatus which are only present during the summer and disturb large volumes of sediment when extracting prey. The experiment consisted of bird exclusion, ray + bird exclusion and reference plots. Samples were collected from each plot o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
54
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(62 citation statements)
references
References 22 publications
(12 reference statements)
6
54
0
Order By: Relevance
“…Therefore, other factors must also be playing an important role. For example, predation has also been shown to impose small-scale differences in macrofaunal community measures for intertidal habitats (Thrush et al 1994). In addition, the temporal changes in sediment sorting observed at the site hint at the role of physical parameters (e.g.…”
Section: --mentioning
confidence: 99%
“…Therefore, other factors must also be playing an important role. For example, predation has also been shown to impose small-scale differences in macrofaunal community measures for intertidal habitats (Thrush et al 1994). In addition, the temporal changes in sediment sorting observed at the site hint at the role of physical parameters (e.g.…”
Section: --mentioning
confidence: 99%
“…mussel beds (Andersen & Kristensen, 1988;Asmus & Asmus, 1996), and physical removal (and deposition) of organic carbon caused by, for example, winds, tides and currents (Bayerl et al, 1996), which can be important and probably balance the budgets. Furthermore, export of carbon via crab, fish and bird predation should also be considered (Raffaeli & Milne, 1987;Hall et al, 1990;Thrush et al, 1994).…”
Section: Annual Budgetsmentioning
confidence: 99%
“…obs. ), but at much lower densities than in Manukau Harbour (Thrush et al 1994;Hine:禄 et al 1997), and we doubt that they play an importai it role. Putt's (1996) study of three invertebrate predators of bivalves present across Centre Bank, (the sea stars Coscinasterias calamaria and Patiriella regularis and the whelk Cominella adspersa) suggested that abundances of these predators are generally no : high, and that the low movement rates of those preiators in patches of an abundant resource were a result of satiation.…”
Section: Discussionmentioning
confidence: 99%
“…Vertebrate predators of bivalves such as eagle rays and wading birds influence distributions of intertidal bivalves in Manukau Harbour (Thrush et al 1994). Wading birds seldom have access to bivalve populations of a sub tidal area such as Centre Bank.…”
Section: Discussionmentioning
confidence: 99%